Basic Fibroblast Growth Factor Inhibits the Anabolic Activity of Insulin-like Growth Factor 1 and Osteogenic Protein 1 in Adult Human Articular Chondrocytes - Loeser, Richard F. (2005)
OBJECTIVE: To determine the effects of basic fibroblast growth factor (bFGF) on the chondrocyte anabolic activity promoted by insulin-like growth factor 1 (IGF-1) and osteogenic protein 1 (OP-1). METHODS: Human articular chondrocytes were cultured in alginate beads or as cartilage explants in serum-free medium with or without IGF-1 (100 ng/ml), OP-1 (100 ng/ml), or bFGF (0–100 ng/ml). Cell survival, proliferation, proteoglycan synthesis, and total proteoglycan accumulation were measured after 21 days of culture in alginate beads, and proteoglycan synthesis was measured in explants. RESULTS: Cell survival was not altered by bFGF at any dose, and chondrocyte proliferation was stimulated only at doses above 1 ng/ml. When combined with IGF-1, 1 ng/ml of bFGF stimulated proliferation to 170% of control, but when combined with IGF-1 and OP-1, proliferation increased to 373% of control. Doses of bFGF of 100 ng/ml decreased total proteoglycan levels accumulated per cell by 60% compared with control and also inhibited the ability of IGF-1 or OP-1 to increase proteoglycan production. Likewise, sulfate incorporation in response to IGF-1 and OP-1 alone or together was completely inhibited by 50 ng/ml bFGF in both alginate and explant cultures. CONCLUSION: The anabolic activity of IGF-1 and OP-1, alone and in combination, is significantly inhibited by bFGF. The results suggest that excessive release of bFGF from the cartilage matrix during injury, with loading, or in arthritis could contribute to increased proliferation and reduced anabolic activity in articular cartilage.